THE ANALYSIS OF VILLAGE MIDWIFE PERFORMANCE IN REDUCING MATERNAL AND INFANT MORTALITY RATE - Tumartony Thaib Hiola; Bun Yamin M. Badjuka (Universitas Airlangga, 2020)
Background: The most essential aspect to reduce the number of maternal and newborn mortality is midwife competence. Midwives have a great role to be able to handle variety of health services (antepartum, intrapartum, and postpartum) to avoid or decrease the maternal and infant mortality rate. Performance of health workers, particularly midwives, is the most crucial in affecting the quality and quantity of midwives' services to  enhance the national health development. Aim: This study analyzed factors affecting village midwife performance for reducing maternal and infant mortality in seek for achieving Bone Bolango cemerlang or bright Bone Balango as the vision of Bone Bolango District in 2021. Methods: This study was an analytical survey with a cross-sectional approach. It was conducted from March to June 2019 in the working area of Bone Bolango District Health Office. There were 227 people from 19 primary healthcare centers as the population, and the sample size was 227 selected by using the total sampling technique. The data were collected by distributing questionnaires to the respondents and using secondary data. The data processing was done through chi-square test and multiple logistic regression with backward wald method. Results: Midwife performance in Bone Bolango District was assessed based on several variables. Most of them were ≥ 25 years old (80.6%); worked for ≥ five years (58,6%); mostly had not participated in any normal childbirth care training (76.7%); had a good competence (96.5%); had good resources/equipment (79.7%); had a good reward (92.5%); had a good attitude (76.2%); had a good motivation (90.7%). There were 12 maternal mortalities from 2017 to 2019 handled by only 11 midwives (4.8%). On the other hand, infant mortality rate (IMR) reached 25 cases in the same years; of 227 midwives, these cases were handled by only 21 midwives (9.3%). Conclusion: A midwife as a part of the health workers has an important role to increase the quality of maternal and child well-being program. Some variables that became indicators of midwife performance and had an effect on reducing the MMR and IMR included work period, reward, and motivation. This study recommends that all midwives have to be provided with a normal childbirth care training in the working area and increased rewards in the process of labor and delivery.   Keywords: midwives, performance, maternal mortality rate, infant mortality rate.